Missed opportunities for antimicrobial stewardship in pre‐school children admitted to hospital with lower respiratory tract infection. (23rd March 2017) - Walls, Tony; Stark, Erika; Pattemore, Philip; Jennings, Lance
Abstract : Aim: To describe the usage of multiplex polymerase chain reaction on nasopharyngeal swab (NPS) samples in pre‐school children presenting with lower respiratory tract infection (LRTI) at Christchurch Hospital, and its impact on the use of antibiotics empirically and at discharge. Methods: This retrospective cohort study included 237 children, ages 3 months to 5 years, admitted to hospital during the winter months of 2012–2015 with a diagnosis of community‐acquired LRTI. Children were identified by discharge coding and their notes reviewed. Results: A significantly larger proportion of children who had a NPS sample taken (42/146, 36%) received no empiric antibiotics compared with children who did not have a sample taken (7/91, 7.7%, P < 0.001). Of those who did have a NPS sample taken 17 of 146 (11.6%) had their antibiotics discontinued prior to or at the time of discharge compared with only 3 of 91 (3.3%) of those who did not have a NPS sample ( P < 0.025). Children with influenza detected were more likely to receive no antibiotics or have their antibiotics discontinued prior to or at discharge. Only a small proportion of children with other viruses identified had their antibiotics discontinued. Conclusions: It appears that clinicians were generally reluctant to stop antibiotics prior to discharge in young children with LRTI in whom influenza or other viruses were identified. In our view, it makes sense to stop antibiotics when the clinical presentation and NPS testing is consistent with a viral aetiology. Not stopping antibiotics at or before discharge in these children represents a missed opportunity for antimicrobial stewardship.